ANALISIS BIBLIOMETRIK: CADMIUM SULFIDE (CdS) SEBAGAI KATALIS MENGGUNAKAN VOSVIEWER - Sinta Susilo; Asep Bayu Dani Nandiyanto (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2023)
This study aims to examine the development of research on cadmium sulfide (CdS) as a catalyst with a bibliometric approach using computational mapping analysis using the VOSviewer application. To support research, a reference manager application (Publish or Perish) is used to obtain article data from the Google Scholar database. The keyword